Landasan Filosofis dan Teknologi Digital dalam Memaknai Nilai Pendidikan di Masa Depan - Sinaga, Rike; F, Firman; N, Nurfahanah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The digital era has brought great changes to the world of education, especially through the Industrial Revolution 4.0 and Society 5.0. However, technological advances without a strong philosophical foundation have the potential to shift the essence of education from a humanizing process to a merely technocratic one. This article offers an integration between the philosophy of education and digital technology through the “Technosophy” approach, which emphasizes ontological, epistemological, and axiological dimensions. Using a qualitative method based on literature study, this research examines how values such as justice, freedom, and responsibility should be the basis for the use of technology. It also emphasizes the importance of the teacher’s role as a value facilitator and not just a technical instructor. The study recommends an adaptive and meaningful value-based learning model and education policy in response to the challenges of digital disruption and inequality in contemporary education.